Cognitive and neuroimaging findings in developmental coordination disorder: new insights from a systematic review of recent research - Wilson, Peter H.; Blank, Rainer (Developmental medicine and child neurology, 2017)
Aim To better understand the neural and performance factors that may underlie developmental coordination disorder (DCD), and implications for a multi-component account. Method A systematic review of the experimental literature published between June 2011 and September 2016 was conducted using a modified PICOS (population, intervention, comparison, outcomes, and study type) framework. A total of 106 studies were included. Results Behavioural data from 91 studies showed a broad cluster of deficits in the anticipatory control of movement, basic processes of motor learning, and cognitive control. Importantly, however, performance issues in DCD were often shown to be moderated by task type and difficulty. As well, we saw new evidence of compensatory processes and strategies in several studies. Neuroimaging data (15 studies, including electroencephalography) showed reduced cortical thickness in the right medial orbitofrontal cortex and altered brain activation patterns across functional networks involving prefrontal, parietal, and cerebellar regions in children with DCD than those in comparison groups. Data from diffusion-weighted magnetic resonance imaging suggested reduced white matter organization involving sensorimotor structures and altered structural connectivity across the whole brain network. Interpretation Taken together, results support the hypothesis that children with DCD show differences in brain structure and function compared with typically developing children. Behaviourally, these differences may affect anticipatory planning and reduce automatization of movement skill, prompting greater reliance on slower feedback-based control and compensatory strategies. Implications for future research, theory development, and clinical practice are discussed.